PENGARUH STRUKTUR KEPEMILIKAN DAN STRUKTUR MODAL TERHADAP HARGA SAHAM - Raharjanti, Rani; Setyowati, Nur (JURNAL AKUNTANSI DAN AUDITING, 2017)
This paper aims to investigate the short and long run behavior of ownership structure, capital structure and Indonesian Stock Price over the period from 2007 to 2016. To capture the long run relationships, we used the panel cointegration by Pedroni (1999, 2000, 2004), while the short run relationship are measured by Vector Error Correction Model (VECM). The main findings are as follows. First, the result of most results of Pedroni’s panel cointegration tests, suggest the null hypothesis of no cointegration is rejected. In consequence, this result suggests that there is a cointegration between stock price, managerial ownership, institutional ownership, public ownership, debt to equity ratio and earnings per share. Second, the results of VECM indicate that in the short run, only managerial ownership that will influence the stock price.